Uremic Toxin Lanthionine Induces Endothelial Cell Mineralization In Vitro - Annapaola Coppola; Carmela Vigorito; Patrizia Lombari; Yuselys García Martínez; Margherita Borriello; Francesco Trepiccione; Diego Ingrosso; Alessandra F. Perna (Biomedicines, 2022)
Vascular calcification (VC) is a pathological event caused by the unusual deposition of minerals in the vascular system, representing the leading cause of cardiovascular mortality in chronic kidney disease (CKD). In CKD, the deregulation of calcium and phosphate metabolism, along with the effect of several uremic toxins, act as key processes conveying altered mineralization. In this work, we tested the ability of lanthionine, a novel uremic toxin, to promote calcification in human endothelial cell cultures (Ea.hy926). We evaluated the effects of lanthionine, at a concentration similar to that actually detected in CKD patients, alone and under pro-calcifying culture conditions using calcium and phosphate. In pro-calcific culture conditions, lanthionine increased both the intracellular and extracellular calcium content and induced the expression of Bone Morphogenetic Protein 2 (BMP2) and RUNX Family Transcription Factor 2 (RUNX2). Lanthionine treatment, in pro-calcifying conditions, raised levels of tissue-nonspecific alkaline phosphatase (ALPL), whose expression also overlapped with Dickkopf WNT Signaling Pathway Inhibitor 1 (DKK1) gene expression, suggesting a possible role of the latter gene in the activation of ALPL. In addition, treatment with lanthionine alone or in combination with calcium and phosphate reduced Inorganic Pyrophosphate Transport Regulator (ANKH) gene expression, a protective factor toward the mineralizing process. Moreover, lanthionine in a pro-calcifying condition induced the activation of ERK1/2, which is not associated with an increase in DKK1 protein levels. Our data underscored a link between mineral disease and the alterations of sulfur amino acid metabolisms at a cell and molecular level. These results set the basis for the understanding of the link between uremic toxins and mineral-bone disorder during CKD progression.